The efficacy and safety of haloperidol for the treatment of delirium in critically ill patients: a systematic review and meta-analysis of randomized controlled trials - Huang, Jian; Zheng, Hui; Zhu, Xianfeng; Zhang, Kai; Ping, Xiaofeng (Frontiers in Medicine, 2023)
Purpose Delirium is common during critical illness and is associated with poor outcomes. Therefore, we conducted this meta-analysis to investigate the efficacy and safety of haloperidol for the treatment of delirium in critically ill patients. Methods Randomized controlled trials enrolling critically ill adult patients to compare haloperidol with placebo were searched from inception through to February 20th, 2023. The primary outcome were delirium-free days and overall mortality, secondary outcomes were length of intensive care unit stay, length of hospital stay, and adverse events. Results Nine trials were included in our meta-analysis, with a total of 3,916 critically ill patients. Overall, the pooled analyses showed no significant difference between critically ill patients treated with haloperidol and placebo for the delirium-free days (MD −0.01, 95%CI −0.36 to 0.34, p = 0.95, I2 = 30%), overall mortality (OR 0.89, 95%CI 0.76 to 1.04, p = 0.14, I2 = 0%), length of intensive care unit stay (MD −0.06, 95%CI −0.16 to 0.03, p = 0.19, I2 = 0%), length of hospital stay (MD −0.06, 95%CI −0.61 to 0.49, p = 0.83, I2 = 0%), and adverse events (OR 0.90, 95%CI 0.60 to 1.37, p = 0.63, I2 = 0%). Conclusion Among critically ill patients, the use of haloperidol as compared to placebo has no significant effect on delirium-free days, overall mortality, length of intensive care unit and/or hospital stay. Moreover, the use of haloperidol did not increase the risk of adverse events.